2014
DOI: 10.1080/02701367.2014.961051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Sport Education Program on Motivation for Physical Education and Leisure-Time Physical Activity

Abstract: Sport education facilitates more internalized forms of student motivation in required physical education programs, but without the provision of an appropriately designed extracurricular outlet, the potential of transfer to leisure-time physical activity may not be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
117
0
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(142 citation statements)
references
References 31 publications
8
117
0
17
Order By: Relevance
“…Social recognition and status goals also significantly positively predicted extra-curricular exercise participation. However, students' motivation for leisure-time physical activity was not entirely confirmed in the authors' follow-up study examining students' perceptions over participation in a 2-year SE program (116) . It was suggested that the lack of appropriately designed extracurricular programmes might have restrained students' intention for participation in physical activities beyond those offered in the PE context.…”
Section: Enthusiasm: Students' Motivational Responses and Sport Culturementioning
confidence: 99%
See 3 more Smart Citations
“…Social recognition and status goals also significantly positively predicted extra-curricular exercise participation. However, students' motivation for leisure-time physical activity was not entirely confirmed in the authors' follow-up study examining students' perceptions over participation in a 2-year SE program (116) . It was suggested that the lack of appropriately designed extracurricular programmes might have restrained students' intention for participation in physical activities beyond those offered in the PE context.…”
Section: Enthusiasm: Students' Motivational Responses and Sport Culturementioning
confidence: 99%
“…According to Clarke and Quill (17) , the SE model gave pupils a more authentic and less abstracted learning experience, which has improved their understanding and performance in games and gymnastics. Conversely, although taken in reference to students' participation in consecutive seasons of SE involving team sports, the studies of Wallhead, Garn, and Vidoni (116) , Wallhead, Garn, Vidoni, and Youngberg (117) , and Sinelnikov and Hastie (104) were based on pre-post test surveys and on data collected in one moment in time after the participants' enrolment in SE. As a limitation in these studies no examination was conducted on the development of the teaching--learning process that might shed light on the whys and hows associated with the findings.…”
Section: Exploring the Effects Of Timementioning
confidence: 99%
See 2 more Smart Citations
“…Because of these social changes, leisure is recognized as an important part of an active and creative life that contributes to the stability of life, not merely diversion or relaxation (Wallhead, Garn, &Vidoni, 2014). Among them, golf has become a very familiar sport for a short time, and it is attracted to modern people because it is a nature-friendly sport and leisure activity that promotes mental and physical development (Funk, Beaton,& Pritchard, 2011).…”
Section: Introductionmentioning
confidence: 99%